Efficacy of different caffeine concentrations on growth and ochratoxin A production by Aspergillus species - Akbar, Asya Hussain; Medina, Angel; Magan, Naresh (Wiley, 2016)
The objective of this study was to evaluate the effect of different caffeine concentrations (0–4%) on (i) lag phase prior to growth, (ii) growth rates and (iii) ochratoxin A (OTA) production by strains from the Aspergillus section Circumdati and Aspergillus section Nigri groups, isolated from coffee, when grown on a conducive medium at 0·98 water activity and 30°C. The lag phases prior to growth increased with caffeine concentration. A strain of Aspergillus niger and Aspergillus carbonarius were the most sensitive to caffeine with growth being inhibited by <1% caffeine. For strains of Aspergillus westerdijkiae, Aspergillus ochraceus and Aspergillus steynii, although growth was inhibited significantly, some growth (10–15% of controls) occurred in 4% caffeine. OTA production was significantly inhibited by only 0·5% caffeine for strains of A. westerdijkiae, A. niger and A. carbonarius. For A. steynii at least 1·5% caffeine was required to inhibit OTA production. In contrast, for the strain of A. ochraceus there was a stimulation of OTA at 3% with a reduction at 4% caffeine. These results are discussed in the context of the different concentrations of caffeine found in Arabica and Robusta coffee and the development of minimization strategies.
Keywords: Aspergillus; Caffeine concentration; Growth; Lag phase; Ochratoxin A